ANALISIS RASIONALITAS INVSETOR DALAM PEMILIHAN DAN PENENTUAN PORTOFOLIO OPTIMAL PADA SAHAM-SAHAM JAKARTA ISLAMIC INDEX - Rifqiawan, Raden Arfan (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2012)
The purpose of this study is to determine that wether investor rationality exist in undergoing the stock choice in Jakarta Islamic Index at Indonesia Stock Exchange. Population to be chosen in the study is 44 firms listed on JII. However, the sample included are only 19 firms that present 30 times consecutively of simultan monitoring on JII. From 19 firms after analyzed with single index model found 11 has firms has ERB > Ci*, that mean if investor invests in 11 stocks will get return higher with lower risk in comparison with investment in risk free asset. Data to be used in the study is the secondary one, which is collected from Indonesia Stock Exchange Monthly Statistic and risk free rate report from Central Bank of Indonesia.Result to be obtained from the study demonstrates on empirical evidence of investor rationally in choosing the stock on JII. The value is showed averagely stocks trade volume that has ERB > Ci* higher is compared averagely stocks trade volume that has ERB< Ci*.